GO enhanced visible-light response of g-C3N4 aerogel and degradation of unsymmetrical dimethylhydrazine in wastewater - ZHOU Feng (Journal of Materials Engineering, 2021)
A series of GO/g-C3N4 aerogel materials were prepared by the methods of ultrasonic peeling, solution cross-linking and freeze-drying, and the proportion of raw materials were optimized. The materials were characterized by SEM, XRD, and UV-vis absorption spectrum. The photocatalytic activity was evaluated by the degradation of unsymmetrical dimethylhydrazine (UDMH) wastewater. The pure g-C3N4 aerogel was dominated by mesoporous structure. As the graphene oxide (GO) ratio increases, the layered structure and macroporous structure of the material gradually increase, and all show strong adsorption performance. When the mass fraction of GO is 25%, the photocatalytic degradation of UDMH wastewater is the best and the performance is stable after 5 cycles, the photocatalytic activity is only reduced by 7.15%. Through the study on the energy band structure, characterization of photoelectric effect and PL spectrum, the results show that the g-C3N4 molecular orbital energy level and band gap (Eg) were impacted by the cross-linking between the π-π bond of GO layers and the aromatic ring of g-C3N4, which improve the response performance to visible light. The metallic properties of GO facilitate the rapid separation of photogenerated electron-hole pairs and improve the photocatalytic activity. According to the band gap calculation and the intrinsic molecular orbital of the material, the main active species for GOCN photocatalytic degradation of UDMH wastewater are ·O-2 and h+.